$Zn-Pb$ Okruszcowanie złoża Kizhnica, Kosowo - Wojciechowski, Kamil (My University, 2014)
This thesis includes characterisation of the mineralization occurs in Kizhnica open pit mine in Kosovo. This is $Zn-Pb$ polymetallic mineralization. Kizhnica open pit mine is currently not in operation, nearby Kizhnica is located $Zn-Pb$ Mine “Artana”. Kizhnica open pit is located in the Trepça Mineral Belt, which belongs to Vardar Zone. During the diploma practice had been gathered some samples of ore, which were used to prepare polished sections for reflected light microscope. Next step of study were tests of polished sections prepared for EDS and WDS probe. Complete analysis have been interpreted based on literature. The genetic type of deposit has been characterized based on this study.

W pracy scharakteryzowano mineralizację występującą w złożu Kizhnica w Kosowie. Jest to mineralizacja $Zn-Pb$. Złoże obecnie nie jest eksploatowane, w jego pobliżu znajduje się kopalnia $Zn-Pb$ Artana. Złoże Kizhnica znajduje się w pasie Trepça Mineral Belt w Strefie Vardar. Do badań posłużyły zebrane w Kizhnicy podczas praktyki dyplomowej fragmenty skał zawierające rudę polimetaliczną $Zn-Pb$. Wykonano z nich zgłady mikroskopowe do światła odbitego, następnie wykonano badania sondą EDS oraz WDS. Wykonane badania zostały zinterpretowane w oparciu o literaturę został scharakteryzowany typ genetyczny złoża.
$Zn-Pb$ mineralization in Kizhnica deposit, Kosovo
Keywords: złoże Kizhnica; mineralizacja Zn-Pb; Kizhnica deposit; Zn-Pb mineralization; Kosowo; Kosovo